Short-term severe drought influences root volatile biosynthesis in eastern white pine (Pinus strobus L) - Chandrasekaran, Umashankar; Byeon, Siyeon; Kim, Kunhyo; Kim, Seo Hyun; Park, Chan Oh; Han, Ah reum; Lee, Young-Sang; Kim, Hyun Seok (Frontiers in Plant Science, 2022)
Climate change-related drought stress is expected to shift carbon partitioning toward volatile organic compound (VOC) biosynthesis. The effect of drought stress on VOC synthesis remains unknown in several commercially important tree species. Therefore, we exposed eastern white pine (Pinus strobus) plants to severe drought and performed physiological analysis (chlorophyll content, leaf water content, and root/shoot index), biochemical analysis (non-structural carbohydrates, proline, lipid peroxidation, and antioxidant assay), and total root VOC analysis. Drought stress decreased the relative water and soil moisture contents. Root proline accumulation and antioxidant activity increased significantly, whereas leaf chlorophyll synthesis and fresh weight decreased significantly in drought-treated plants. A non-significant increase in sugar accumulation (leaves and roots), proline accumulation (leaves), antioxidant activity (leaves), and lipid peroxidation (leaves & roots) was observed in drought-treated plants. Drought stress caused a non-significant decline in root/shoot ratio and starch accumulation (leaves and roots) and caused a significant increase in root abscisic acid content. Drought-treated plants showed an increase in overall monoterpene synthesis and decline in total sesquiterpene synthesis. Our findings provide an overall assessment of the different responses of VOC synthesis to severe water deficit that may help unravel the molecular mechanisms underlying drought tolerance in P. strobus.